HUBUNGAN STATUS GIZI, AKTIVITAS FISIK DAN USIA MENARCHE DENGAN SIKLUS MENSTRUASI SISWI SMA DI KOTA DENPASAR - Ayu Dwi Lestari, Ni Made Sekar; Arya Utami, Ni Wayan (ARCHIVE OF COMMUNITY HEALTH; Vol 11 No 3 (2024): Desember 2024, 2025)
The normal menstrual cycle occurs in the range of 21-35 days, a normal menstrual cycle describes the reproductive organs in a healthy state with a good hormonal system. Disorders of the menstrual cycle that are not normal in young women are quite high and can cause infertility. The menstrual cycle is influenced by the age of menarche, nutritional status, stress level, physical activity and nutrient intake. To improve menstrual cycle disorders, this study aims to determine the relationship between nutritional status, physical activity and age at menarche with the menstrual cycle. This study used a cross-sectional design. This research was conducted in Denpasar City. The research sample is 15-18 years old with a total of 182 people. Data analysis was carried out using univariable analysis and bivariable analysis using the chi square test. The results showed that nutritional status (p-value = 0.000) and physical activity (p-value = 0.037) were significantly related to the menstrual cycle, while the age of menarche had no relationship with the menstrual cycle (p-value = 0.111). There should be education about reproductive health programs regarding the menstrual cycle. Keywords: Adolescents, menstrual cycle, nutritional status, physical activity, menarche